KEBERLANJUTAN EKONOMI, SOSIAL-BUDAYA DAN LINGKUNGAN BALI SPIRIT FESTIVAL, UBUD, BALI - I Gusti Ngurah Agung Suprastayasa; Luh Putu Citrawati; I Ketut Arjaya; Nyoman Reni Ariasri; I Nyoman Lingga Sana (UHN IGB Sugriwa Denpasar, 2025)
This study aims to explore and analyze the extent to which the principles of economic, socio-cultural, and environmental sustainability are implemented in the Bali Spirit Festival held in Ubud, Bali. The festival is an internationally recognized annual event combining spirituality, wellness, and local culture. A qualitative descriptive approach was employed through in-depth interviews with the festival's founder and relevant stakeholders. The findings reveal that the Bali Spirit Festival significantly contributes to economic sustainability by empowering local MSMEs, generating employment, and promoting local products. From the socio-cultural perspective, the festival promotes local and global cultural expression, although challenges remain in avoiding cultural commodification. Environmentally, the festival has adopted several eco-friendly practices, but waste management and energy consumption still require improvement. This research underscores the importance of collaboration between festival organizers, local communities, and government bodies to realize holistic sustainability practices in event management. The findings are expected to inform future sustainable event policies in similar tourism destinations.